Optimal strategy for maximizing energy efficiency of 4G and 5G coexistence network - Yahui XUE; Zecai SHAO; Chunfeng CUI; Jing JIN; Hanning WANG (Dianxin kexue)
The energy efficiency of wireless networks has gradually become an important indicator for evaluating network performance.It’s very important to improve the energy efficiency of the coexisting 4G and 5G networks as there are differences in energy efficiency of them.Firstly, the energy consumption composition of base station was analyzed, energy consumption models for 4G and 5G base stations through measured data were established, and then its energy efficiency was evaluated through simulations.The results show that 4G and 5G have their own optimal energy-efficiency areas separated by the critical point of 500 Mbit/s, above which the 5G energy efficiency is better.When dual networks operate simultaneously under the proposed-solution where only 4G is used when the throughput is less than 500 Mbit/s and only 5G is used otherwise, the power consumption of a single station can be reduced by 53.4% and the energy efficiency can be improved by 116.4%.